Microsatellite alterations are also present in the less aggressive types of adult T-cell leukemia-lymphoma. - Marcelo Magalhães; Pedro D Oliveira; Achiléa L Bittencourt; Lourdes Farre (Public Library of Science (PLoS), 2015)
Adult T-cell leukemia/lymphoma (ATL) is a mature T-cell neoplasia etiologically linked to HTLV-1. Manifestations of ATL are diverse and different clinical types with different tissue involvement and aggressiveness have been described. The mechanisms that lead to the development of ATL clinical types have not yet been clarified. Considering that in ATL patients HTLV-1 infection generally occurs in childhood, a multistep carcinogenesis model has been proposed. Microsatellite alterations are important genetic events in cancer development and these alterations have been reported in the aggressive types of ATL. Little is known about oncogenesis of the less aggressive types.In this study we investigated the role of the microsatellite alterations in the pathogenesis mediated by HTLV-1 in the different types of ATL. We examined the presence of microsatellite instability (MSI) and loss of heterozigosity (LOH) in matched pair samples (tumoral and normal) of 24 patients with less aggressive types (smoldering and chronic) and in aggressive types (acute and lymphoma) of ATL. Four microsatellite markers D10S190, D10S191, D1391 and DCC were analyzed. MSI was found in four patients, three smoldering and one chronic, and LOH in four patients, three smoldering and one acute. None of the smoldering patients with microsatellite alterations progressed to aggressive ATL.To our knowledge, this is the first report describing the presence of MSI and LOH in the less aggressive types of ATL. These results indicate that microsatellite alterations may participate in the development of the less aggressive types of ATL.